Opioid Agonist Treatment and Risk of Mortality During an Opioid Overdose Public Health Emergency: A Population-Based Retrospective Cohort Study - Lindsay A Pearce; Jeong Eun Min; Micah Piske; Haoxuan Zhou; Fahmida Homayra; Amanda Slaunwhite; Michael A Irvine; Gina McGowan; Bohdan Nosyk (International Journal of Population Data Science, 2020)
Introduction Opioid agonist treatment (OAT) is a safe and effective treatment for opioid use disorder (OUD). However, people commonly stop and start OAT and their risk of death is high immediately after stopping. The prevalence of illicitly manufactured fentanyl and other highly potent synthetic opioids have increased in the illicit drug supply globally. Yet, there is limited evidence examining the relationship between OAT and mortality when these contaminants are widely available in the illicit drug supply.